STUDI PERBANDINGAN METODE MODAL TESTING KLASIK DAN MODAL TESTING KOMPLEKS DENGAN METODE ANALITIK DALAM IDENTIFIKASI ARAH WHIRLING ORBIT SISTEM ROTOR. - Bagus Budiwantoro; Zulhendri H (Mesin, 2001)
The classical modal testing theory has been widely and successfully used for modal parameter identification of structures of all kinds, except rotating machinery. In this paper a new modal testing theory is explained to separate the rotor vibration into positive and negative frequenc regions. The dynamic characteristics of nonrotating structures in negative frequency region have no meanings, but the dynamic characteristics of rotor systems in negative frequency region havesignificant physical meanings. Since all dynamic characteristics of rotor systems are closely related with rotor rotations, the directivity of modes is very important in rotor dynamics. The frequency response function are obtained by the new modal testing method using complex notation can be used to identify the directivity of modes such as forward and backward. Applications of the classical and complex modal testing method are compared with the analytical method to identify the whirl directions of single/multi rotor systems.